Characterization of Heterozygous HTRA1 Mutations in Taiwanese Patients With Cerebral Small Vessel Disease - Lee, Yi-Chung; Chung, Chih-Ping; Chao, Nai-Chen; Fuh, Jong-Ling; Chang, Feng-Chi; Soong, Bing-Wing; Liao, Yi-Chu (Stroke (1970), 2018)
BACKGROUND AND PURPOSE—Homozygous and compound heterozygous mutations in the high temperature requirement serine peptidase A1 gene (HTRA1) cause cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy. However, heterozygous HTRA1 mutations were recently identified to be associated with autosomal dominant cerebral small vessel disease (SVD). The present study aims at investigating the clinical features, frequency, and spectrum of HTRA1 mutations in a Taiwanese cohort with SVD. METHODS—Mutational analyses of HTRA1 were performed by Sanger sequencing in 222 subjects, selected from a cohort of 337 unrelated patients with SVD after excluding those harboring a NOTCH3 mutation. The influence of these mutations on HTRA1 protease activities was characterized. RESULTS—Seven novel heterozygous mutations in HTRA1 were identified, including p.Gly120Asp, p.Ile179Asn, p.Ala182Profs*33, p.Ile256Thr, p.Gly276Ala, p.Gln289Ter, and p.Asn324Thr, and each was identified in 1 single index patient. All mutations significantly compromise the HTRA1 protease activities. For the 7 index cases and another 2 affected siblings carrying a heterozygous HTRA1 mutation, the common clinical presentations include lacunar infarction, intracerebral hemorrhage, cognitive decline, and spondylosis at the fifth to sixth decade of life. Among the 9 patients, 4 have psychiatric symptoms as delusion, depression, and compulsive behavior, 3 have leukoencephalopathy in anterior temporal poles, and 2 patients have alopecia. CONCLUSIONS—Heterozygous HTRA1 mutations account for 2.08% (7 of 337) of SVD in Taiwan. The clinical and neuroradiological features of HTRA1-related SVD and sporadic SVD are similar. These findings broaden the mutational spectrum of HTRA1 and highlight the pathogenic role of heterozygous HTRA1 mutations in SVD.